A bioactive collagen membrane that enhances bone regeneration. Issue 6 (22nd November 2018) - Khorsand, Behnoush; Elangovan, Satheesh; Hong, Liu; Kormann, Michael S. D.; Salem, Aliasger K.
Abstract: Membranes are an integral component of guided bone regeneration protocols. This pre‐clinical study was aimed at enhancing the bioactivity of collagen membranes by incorporating plasmid DNA ( p DNA) or chemically modified RNA (cmRNA) encoding bone morphogenetic protein‐9 (BMP‐9). In addition, we also endeavored to harness the regenerative potential of the periosteum by creating perforations in the membrane. Nanoplexes of polyethylenimine (PEI)‐nucleic acids (PEI‐ p DNA or PEI‐cmRNA encoding BMP‐9) were incorporated into commercially obtained and perforated collagen membranes (PCM) to produce PCM‐ p DNA(BMP‐9) or PCM‐cmRNA(BMP‐9). After structural characterization, the biodegradation kinetics of PCM, PCM‐ p DNA(BMP‐9) and PCM‐cmRNA(BMP‐9) were assessed in simulated body fluid in vitro. Using a 24‐well transwell plate system with bone marrow stromal cells (BMSCs) in the lower chamber and the PCM to be tested in the upper chamber, the in vitro bioactivity of different PCMs was evaluated by measuring various markers for osteogenesis in BMSCs. Alkaline phosphatase activity was assessed in BMSCs, after 7 and 11 days of exposure to PCM, PCM‐ p DNA(BMP‐9), or PCM‐cmRNA(BMP‐9). Similarly, calcium deposition and Alizarin red staining in BMSCs were assessed after 14 days of exposure to the three different types of PCM. PCMs were then tested in vivo using the calvarial defect model in rats. After 4 weeks, animals were euthanized and bone specimens were harvested for micro‐computed tomography and histological assessments. Incorporation of p DNA or cmRNA did not alter the biodegradation profile of PCMs. Alkaline phosphatase activity trended toward being higher in BMSCs exposed to PCM‐cmRNA(BMP‐9) or PCM‐ p DNA(BMP‐9), when compared to BMSCs alone. Similar trends were observed when calcium deposition and alizarin red staining was evaluated. Calvarial bone defects treated with PCM‐cmRNA(BMP‐9) resulted in significantly higher bone volume/total volume % (BV/TV%), when compared to empty defects and trended toward being higher than defects treated with PCM‐ p DNA(BMP‐9) and PCM alone. We demonstrate for the first time that resorbable PCM can be utilized to efficiently deliver p DNA and cmRNA of interest. The released p DNA and cmRNA encoding BMP‐9 in this assessment was shown to be functional in vitro as well as in vivo . © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1824–1832, 2019.